Adjunctive brivaracetam for uncontrolled focal and generalized epilepsies: Results of a phase III, double‐blind, randomized, placebo‐controlled, flexible‐dose trial. Issue 1 (3rd October 2013) - Kwan, Patrick; Trinka, Eugen; Van, Wim; Rektor, Ivan; Johnson, Martin E.; Lu, Sarah
Summary Purpose To evaluate the safety and tolerability of adjunctive brivaracetam (BRV), a high‐affinity synaptic vesicle protein 2A (SV2A) ligand, in adults with uncontrolled epilepsy. Efficacy was also assessed in patients with focal seizures as a secondary objective, and explored by descriptive analysis in patients with generalized seizures. Methods This was a phase III, randomized, double‐blind, placebo (PBO)‐controlled flexible dose trial (N01254/NCT00504881) in adults (16–70 years) with uncontrolled epilepsy (up to 20% could be patients with generalized epilepsy). After a prospective 4‐week baseline, patients were randomized (3:1) to b.i.d. BRV or PBO, initiated at 20 mg/day and increased, as needed, to 150 mg/day during an 8‐week dose‐finding period. This was followed by an 8‐week stable‐dose maintenance period. The treatment period comprised the dose‐finding period plus the maintenance period (16 weeks). Key Findings A total of 480 patients were randomized (BRV 359, PBO 121); of these, 431 had focal epilepsy and 49 had generalized epilepsy. Ninety percent BRV‐ and 91.7% PBO‐treated patients completed the study. Similar proportions of patients (BRV 66.0%, PBO 65.3%) reported adverse events (AEs) during the treatment period. AEs led to treatment discontinuation in 6.1% and 5.0% of BRV‐ and PBO‐treated patients, respectively. The incidence of AEs declined from the dose‐finding (BRV 56.0%, PBO 55.4%) to the maintenance (BRV 36.8%, PBO 40.9%) period. The most frequent AEs during the treatment period were headache (BRV 14.2% vs. PBO 19.8%), somnolence (BRV 11.1% vs. PBO 4.1%), and dizziness (BRV 8.6% vs. PBO 5.8%). The incidence of psychiatric AEs was similar for BRV and PBO (BRV 12.3%, PBO 11.6%). In patients with focal seizures, the baseline‐adjusted percent reduction in seizure frequency/week in the BRV group (n = 323) over PBO (n = 108) was 7.3% (p = 0.125) during the treatment period. The median percent reduction in baseline‐adjusted seizure frequency/week was 26.9% BRV versus 18.9% PBO (p = 0.070), and the ≥50% responder rate was 30.3% BRV versus 16.7% PBO (p = 0.006). In patients with generalized seizures only, the number of seizure days/week decreased from 1.42 at baseline to 0.63 during the treatment period in BRV‐treated patients (n = 36), and from 1.47 at baseline to 1.26 during the treatment period in PBO‐treated patients (n = 13). The median percent reduction from baseline in generalized seizure days/week was 42.6% versus 20.7%, and the ≥50% responder rate was 44.4% versus 15.4% in BRV‐treated and PBO‐treated patients, respectively. Significance Adjunctive BRV given at individualized tailored doses (20–150 mg/day) was well tolerated in adults with uncontrolled epilepsy, and our results provided support for further evaluation of efficacy in reducing focal and generalized seizures.